2009
DOI: 10.1096/fj.08-116814
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TRPC3 with siRNA coupled to carbon nanotubes results in decreased insulin‐mediated glucose uptake in adult skeletal muscle cells

Abstract: The involvement of Ca(2+) in the insulin-mediated signaling cascade, resulting in glucose uptake in skeletal muscle, is uncertain. Here, we test the hypothesis that Ca(2+) influx through canonical transient receptor potential 3 (TRPC3) channels modulates insulin-mediated glucose uptake in adult skeletal muscle. Experiments were performed on adult skeletal muscle cells of wild-type (WT) and obese, insulin-resistant ob/ob mice. Application of the diacylglycerol analog 1-oleyl-2-acetyl-sn-glycerol (OAG) induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 72 publications
(115 reference statements)
1
33
1
Order By: Relevance
“…The calcium ionophore A23187 increases glucose uptake in L6 myotubes (42) and primary myoblast cultures (52). In skeletal muscle fibers, Ca 2ϩ influx is important for full stimulation of insulin-mediated glucose uptake (12,30,32). Nonetheless, the role played by cytoplasmic calcium signals on glucose uptake remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium ionophore A23187 increases glucose uptake in L6 myotubes (42) and primary myoblast cultures (52). In skeletal muscle fibers, Ca 2ϩ influx is important for full stimulation of insulin-mediated glucose uptake (12,30,32). Nonetheless, the role played by cytoplasmic calcium signals on glucose uptake remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely studied is the canonical signaling cascade constituted by PI3K/Akt, that controls glucose uptake, metabolic activity, and translational responses to insulin [37]. Ca 2+ has also been identified as an important second messenger acting downstream of the insulin receptor and shown to be essential in insulin-mediated glucose uptake in cardiac and skeletal muscle [38][39][40]. Our group showed that Ca 2+ release from the ER through the InsP 3 R is an important component of the Ca 2+ -mediated insulin response in cardiomyocytes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Mobilization of Ca 2+ is known to facilitate insulinstimulated glucose uptake in diverse cell types [38][39][40].…”
Section: Mitochondrial Insulin-dependent Ca 2+ Signals In Hypertrophimentioning
confidence: 99%
“…In those cells, decreasing intracellular Ca 2+ signals decreased insulin-stimulated glucose uptake and Akt phosphorylation (Whitehead et al, 2001). In skeletal muscle fibers, Ca 2+ influx is important for full stimulation of glucose uptake (Lanner et al, 2009;Lanner et al, 2006).…”
Section: Journal Of Cell Sciencementioning
confidence: 99%